Low-temperature CO oxidation over integrated penthorum chinense-like MnCo2O4 arrays anchored on three-dimensional Ni foam with enhanced moisture resistance. Issue 6 (27th February 2018) - Mo, Shengpeng; Li, Shuangde; Xiao, Hailin; He, Hui; Xue, Yudong; Zhang, Mingyuan; Ren, Quanming; Chen, Bingxu; Chen, Yunfa; Ye, Daiqi
Abstract : Advanced integrated nanoarray (NA) catalysts have been designed by growing metal-doped Co3 O4 arrays on nickel foam with robust adhesion. Abstract : Advanced integrated nanoarray (NA) catalysts have been designed by growing metal-doped Co3 O4 arrays on nickel foam with robust adhesion. Ternary MCo2 O4 NA catalysts were prepared by doping urchin-like Co3 O4 with different transition metals (Cu 2+, Mn 2+, Fe 2+, Ni 2+, Zn 2+, Fe 3+ and Al 3+ ). These catalysts exhibited novel morphologies and can be directly applied as monolithic materials for CO oxidation. Among the MCo2 O4 NA catalysts, CuCo2 O4 nanoneedles manifested the highest catalytic activity in dry air, achieving an efficient 100% CO oxidation conversion of 20 000 h −1 at 146 °C, due to its reducibility at lower temperature, lattice distortion of the spinel structure, and abundant surface-adsorbed oxygen (Oads ). The doped catalytic systems were further optimized by controlling the volume ratio of reactive components in the mixed solvent, the Cu or Mn contents to determine excellent catalysts for direct application to CO oxidation at 1.0 vol% moisture. Penthorum chinense-like MnCo2 O4 NAs showed optimal catalytic performance at 1 vol% moisture ( T 100 = 175 °C), with activity higher than that of the CuCo2 O4 NA catalyst, indicating that the synergistic effect between MnO x and Co3 O4 improved the moisture resistance and stability. It was concluded that the moisture resistance provided by introducing active sites on Co-based catalysts decreased as follows: Mn sites > Co sites > Cu sites > Ni sites. MCo2 O4 NAs, with predominantly exposed 110 surfaces, showed higher catalytic activity than catalysts with exposed 111 surfaces. This study suggests that the as-prepared MnCo2 O4 NAs anchored on 3D Ni foam with remarkable moisture resistance have potential applications in CO oxidation.